Right-wing radicalism and factors of xenophobic social practice in Hungary and Slovakia: comparative analysis - Il'ia N. Tarasov (Сравнительная политика)
Article retractedAbstract: In Hungary and Slovakia during 2010-2015 there has been an increase in xenophobic attitudes in society; rightwing and extremist groups are activating there as well. The purpose of this article is to compare the most signifi cant factors which encourage xenophobia. Previously we have identifi ed the types of right-wing organizations and found out their electoral characteristics. We assume that the activities of right-wing extremist organizations infl uence the formation of xenophobic social practices in Hungary and Slovakia, which arise from the range of factors. In this article we used empirical data gained as a result of public opinion polls conducted by the leading research centers in Hungary and Slovakia, by international organizations, as well as statistics of public authorities and civil society institutions. By means of factor analysis, we identifi ed the main directions and forms of activity of right-wing radicals; determined the value of socio-economic dynamics of the country's development; characterized the attitude of society, the law and the ruling elite to the problems of xenophobia and right-wing radicalism. Among the most infl uential factors we identifi ed: open propaganda of nationalist ideas; constitutional priority of the ethnic majority interests; parliamentary status of rightwing parties; condoning the activities of right-wing radicals by the ruling elite, the courts and the police. The comparison of factors stimulating xenophobic practices in Hungary and Slovakia didn’t confi rm the hypothesis of common signifi cant infl uence of the economic crisis, lack of education and political passivity on the formation of xenophobic practices among young people. The professional frustration of provincial youth discovered itself as a cumulative socioeconomic factor.